Efektivitas Metode Intiqaiyyah dalam Pembelajaran Bahasa Arab untuk Orang Tua Non-Arabic Speaker - Achmad Rizaldi Fernanda; Faisal Hendra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Arabic language instruction for adult non-native speakers presents a complex challenge in the field of language education, particularly regarding the mastery of four fundamental skills: listening (maharah al-istima’), speaking (maharah al-kalam), reading (maharah al-qira’ah), and writing (maharah al-kitabah). This study aims to analyze the effectiveness of the Intiqaiyyah method—a progressive and adaptive approach—in enhancing the Arabic language proficiency of adult learners. The study employs a qualitative descriptive approach utilizing in-depth interviews, participant observation, and periodic evaluations involving fifteen adult Arabic language students aged 35 to 55. Data were analyzed using thematic analysis with an inductive approach. The results indicate that the Intiqaiyyah method effectively improved comprehension and understanding of basic sentence structures in 80% of participants, increased active participation in Arabic communication by 65%, and enabled 75% of participants to read simple texts while 70% achieved basic communication skills. However, the study also identified several obstacles, including limited time for independent study, a lack of structured teaching materials, and a high dependency of learning success on instructor competence. Based on these findings, the study recommends the development of Intiqaiyyah-based teaching materials, the strengthening of learning support systems via digital media, and the enhancement of instructor competence to ensure the method can be applied more optimally in adult Arabic language education.